设函数[img=66x25]1803457cf4c172e.png[/img]由参数方程[img=153x61]1803457cfe77e36.png[/img]所确定,则[img=46x46]1803457d06fa8cb.png[/img]( ).
未知类型:{'options': ['', '', '', ''], 'type': 102}
未知类型:{'options': ['', '', '', ''], 'type': 102}
举一反三
- 设函数[img=66x25]1803457cf4c172e.png[/img]由参数方程[img=153x61]1803457cfe77e36.png[/img]所确定,则[img=46x46]1803457d06fa8cb.png[/img]( ). A: [img=47x20]1803457d0ff5859.png[/img] B: [img=119x27]1803457d187da47.png[/img] C: [img=126x27]1803457d20a63be.png[/img] D: [img=112x45]1803457d2959ec8.png[/img]
- 设函数y=f(x)由参数方程[img=164x19]17da62a295a4708.jpg[/img]所确定,则[img=19x34]17da4275482315f.jpg[/img]为 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 设 [img=66x25]1803cd94b2014ef.png[/img]由参数方程[img=169x26]1803cd94ba855bf.png[/img]确定,则[img=27x46]1803cd94c3447e3.png[/img]等于( ). 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 设方程[img=134x19]17e43d6cf7199ff.jpg[/img]确定了y是x的函数y=f(x),则f''(x)=( ) 未知类型:{'options': ['', ' [img=96x37]17e43d6d0875b49.jpg[/img]', ' [img=74x38]17e43d6d116f70e.jpg[/img]', ' [img=83x37]17e43d6d1ab1472.jpg[/img]'], 'type': 102}
- 设函数[img=66x25]1803457afeaf1c6.png[/img]由参数方程[img=153x61]1803457b09210d4.png[/img]所确定,则[img=46x46]1803457b1185572.png[/img]( ). A: [img=47x20]1803457b1a3cbb3.png[/img] B: [img=119x27]1803457b2380220.png[/img] C: [img=126x27]1803457b2d9b518.png[/img] D: [img=112x45]1803457b35a8dba.png[/img]